Do xenophobic attitudes influence migrant workers' regional location choice? - Tanja Buch; Carola Burkert; Stefan Hell; Annekatrin Niebuhr; Anette Haas (PLoS ONE)
This paper investigates whether xenophobic attitudes, as measured by the regional share of votes for right-wing parties and xenophobic violence, affect migrants' choices of where to live in Germany. We use a unique panel data set for the period 2004 to 2017 and apply fixed effects regression models and instrumental variable estimation to examine the relationship between anti-immigrant attitudes and immigration. Our results indicate that xenophobic attitudes tend to reduce regional labour immigration. However, evidence seems to be more robust for the support of right-wing parties than for xenophobic violence. Regarding heterogeneous effects across skill groups, the findings are ambiguous. While the immigration of skilled workers seems to be more sensitive to xenophobic violence, evidence is more robust for the share of right-wing votes in the case of low-skilled foreign workers. The strength of the adverse effect of anti-immigrant attitudes tends to increase with the local size of the coethnic community.